The Impact of Social Distancing for COVID-19 Upon Diagnosis of Kawasaki Disease. (23rd March 2021) - Shulman, Stanford; Geevarghese, Bessey; Kim, Kwang-Youn; Rowley, Anne
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mitigation policies have been associated with profound decreases in diagnoses of common childhood respiratory infections. A leading theory of etiology of Kawasaki disease (KD) is that it is triggered by presently unidentified ubiquitous respiratory agent. We document that mitigation policies instituted in mid-March 2020 were associated with strikingly fewer diagnoses of KD in April-December 2020 compared with the same period in the previous 8 years ( P = .01), a >67% decline. This finding supports the hypothesis that KD is caused by a respiratory-transmitted agent.